Organised Crime Typologies: Structure, Activities and Conditions - Le, Vy (2012)
Abstract: Typologies are intended to assist researchers in understanding complex social phenomena. This paper reviews the current literature on organised crime typologies and argues that the majority of organised crime typologies are reflected to some extent in a typology developed by the United Nations Office on Drugs and Crime (UNODC) in 2002. Organised crime typologies can be categorised into three groups: models that focus on the physical structure and operation of an OCG, the activities of OCGs and the social, cultural and historical conditions that facilitate organised crime activity. This paper will only discuss models that examine the physical structure and operation of an OCG; the UNODC typology is exclusively focused on structural elements. Typologies on organised crime structure have developed largely in isolation from each other and appear disparate. This paper will analyse the formation of each typology to establish their individual elements. It will then identify which typologies and their respective characteristics can be aligned with or distinguished from the UN typology. The value of this review is that it will enable greater uniformity and consistency in academic discussion on organised crime typologies